Microwave Assisted Torrefaction Of Plantation Residues And Kitchen Waste - Ramachawolran, Kalaivaani (2016)
Moisture and volatile matter in biomass material should be removed to convert it into char. Among the available methods, torrefaction process of biomass material is the most attractive method converting biomass into char. However, the commonly applied torrefaction process use conventional heating mechanism that consumes high electrical energy. The reaction is usually carried out at 250–300 0C and the heating rates are usually kept below 50 0C/min. The heating of the biomass takes place from the surface to the inside of the particle through conduction, convection and radiation and therefore higher heating rates may result in shorter processing time and also result in incomplete reaction. In contrast to this, in microwave, heating takes place at a molecular level and volumetric heating is achieved. Thus, comparable torrefaction products can be obtained in microwave heating at low power levels and much shorter time, which can save both energy and time in the process. In this project, microwave energy is used to convert plantation residues and kitchen waste into charcoal via torrefaction process. A commercial microwave oven was modified and characterized for torrefaction process. The system is characterized based on time, temperature and microwave power level corresponding to heating rate lower than 50 0C/min. The heating values of the charcoal obtained in this project ranges from 14MJ/kg to 39MJ/kg depending on the types of torrefied material and the torrefaction residence time. The torrefied products were characterized in terms of their elemental composition, energy and mass yields and amount of tar. The gaseous products from torrefaction of different types of materials were also analysed. The output gas from the torrefaction process was analysed using gas chromatography, whilst, moisture content, volatile and fixed carbon had been determined using thermogravimetric analyzer (TGA). The experimental results showed that torrefaction process under low energy consumption of microwave irradiation is suitable process. For waste food and banana peel torrefaction, the oven temperatures was 250 for torrefaction and for palm kernel shell (PKS) and empty fruit bunch (EFB) torrefaction, the oven temperatures were 270 and 300 respectively. The result after torrefaction process, shows that the waste food and banana peel have lower than 10% moisture content compared to palm kernel shell (PKS) and empty fruit bunch (EFB) which have 40% and 10% respectively of moisture content. Moisture content for waste food and banana peel were 5.33% and 2.57% respectively. The heating value (HHV) of torrefied char were 20.81, 21.63, and 22.15 MJ/kg for the torrefaction time of 30 min for palm kernel shell (PKS), and waste food and 40 min for banana peel respectively. This may be contributed by the torrefaction reaction in removing the volatiles and decomposing the lignocelluloses of biomass. For the mass yield, the value started decreasing when torrefaction time increased from 10 to 30 minutes at the temperature 300 0C. For biomass material (PKS, EFB, waste food and banana peel) once temperature reached the higher temperature range of 270 to 300 0C the energy yield reduces because of lower mass yield.